PEMANFAATAN APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT GIGI DAN MULUT DI KLINIK DRG.SUYATMI - Hendra Mardika; Amir Hamzah; Suraya - (Jurnal SCRIPT, 2015)
The progress of computer technology is currently very supportive on every aspect of human life, especially in the field of disease diagnosis. Dental and oral disease is one disease that often affects the community at large. It would be very useful if computer technology is able to diagnose the possibility of dental and oral diseases suffered by a person and give the right advice for patients with diseases of the teeth and mouth. Expert systems is one of the knowledge-based program that can provide solutions to the quality of experts to resolve the problems that usually can only be resolved by an expert, in this case is a dentist. The process of diagnosing a dental and oral diseases suffered by the people can only be solved by an experienced dentist. This study adopts the expert knowledge of dental disease, in this case is a doctor at the clinic drg.Suyatmi into a computer application that is able to diagnose dental and oral disease by displaying the symptoms related diseases that can be chosen by the admin, so it can produce a diagnosis of the disease suffered by patients. In this study it is used advanced search inference method (Forward Chaining). System applications created using Borland Delphi 7.0 with the database using Microsoft Access. From the testing that has been done then it was obtained a conclusion that the application of expert system is able to diagnose oral disease suffered by patients based on symptoms that have been chosen by the admin.